Tackling COVID-19 disinformation: internal and external challenges for the European Union - Vériter, SL; Bjola, C; Koops, JA (Brill Academic Publishers, 2020)
The corona crisis is also a disinformation crisis for the global community in general, and for the European Union (EU) in particular. What is less clear is how adequate the EU’s response to the ‘infodemic’ has been. This essay exposes the dangers of disinformation for the EU, which have intensified in the context of the COVID-19 pandemic, and reviews relevant EU responses. It then zooms in on two challenges exacerbated by the corona crisis: one internal, revolving around the toxic effect of conspiracy theories, particularly the corona-5G hoax; and one external, relating to the public diplomacy campaigns of competing geopolitical actors, especially China. The essay argues that the future of European stability will rest not only on ensuring societal resilience to disinformation and conspiracy theories but also on designing ethically guided pre-emptive mechanisms and confronting external sources of disinformation which jeopardise European health provisions, economic recovery and geoeconomic strength.